Study of Prolonged Administration of Lanthanum Carbonate in Dialysis Patients. (16th April 2013) - Gotoh, Junichi; Kukita, Kazutaka; Tsuchihashi, Seiichiro; Hattori, Masahiro; Iida, Junichi; Horie, Takashi; Onodera, Kazuhiko; Furui, Hidenori; Tamaki, Toru; Meguro, Junichi; Yonekawa, Motoki; Kawamura, Akio
Abstract: Data of 36 months were accumulated regarding the effects of lanthanum carbonate (LA) on serum phosphate concentrations in dialysis patients. Fifty‐three patients (average age and dialysis history 58.4 years and 9.1 years) were included in this study who have been receiving outpatient treatment since March 2009, and who have been unable to maintain serum phosphate concentrations of ≤6.0 mg/dL via traditional therapeutic agents used for hyperphosphatemia. Patients were given dosage of LA in addition to, or instead of, co‐hyperphosphatemia treatments already being received. Mean dosages of calcium carbonate (CC) and sevelamer hydrochloride (SH) before starting LA administration were 1301.9 mg and 2462.3 mg, respectively. Dosage of LA for all cases was 750 mg at initial dose; 1528.3 mg at 5 months; and 1416.7 mg at 30 months. Dosage of other phosphate binders were 905.7 mg of CC and 820.8 mg of SH at 5 months; and 687.5 mg of CC and 1031.3 mg of SH at 30 months. Serum phosphorus levels (P levels) were significantly decreased at 1 month of LA administration, and continued until 30 months of La treatment. These results suggest that LA successfully controlled serum P and Ca concentrations simultaneously within target ranges without affecting serum intact parathyroid hormone concentration, although further long‐term prospective cohort study on LA would be required.